Глечик із Сарати - Гаврилюк, Н.О. (Археологія, 2018)
Наведено нове зображення добре відомого фахівцям глечика з кургану 10, поховання 13 біля с. Сарата на Одещині, розкопаного в 1888—1990 рр. Ф.І. Кнауером. Візуальне вивчення посудини свідчить, що орнаментація, нанесена дрібнозубчастим штампом, пізніше підправлена, внаслідок чого волюти, які характерні для кераміки культури Басарабь, закінчуються голівками змій. Висловлено припущення, що глечик, орнаментований у стилі кераміки цієї культури, міг «дожити» до ранньоскіфського часу. The results of the visual study of well-known and repeatedly published jag from grave no. 13 of the barrow no. 10 near Sarata village in Odesa Region are shown in the paper. The barrow was excavated by professor of the Kyiv St. Volodymyr University F.I. Knauer in 1888—1890. According to the publication of the first results of study, the localization and composition of the barrow group is specified. In the paper the burial no. 13 and the vessel which was placed behind the scull are described. The study of the decoration of Sarata jug de visu in the National Museum of History of Ukraine allowsto conclude that the volutes typical for the Basarabi Culture were ending not only with curls as was previously considered but with two heads of snakes (fig. 4, 3). The volute with the snake head was filled with white paste on the right side, and with pink paste on the left. The enlargement of images suggests that the heads appeared later. They were marked by deep notches, not by a small-notched stamp by which the ornament of the vessel was spouted. The white paste filling the head of snake is more dense on the right side. These observations somewhat change the opinion on the image on Sarata vessel. Probably the images were made in different time. So, the initial decoration was engraved during the manufacture of the vessel among Culture ofBasarabi.The image of the snake headswas added later. Perhaps it was done while preparing the vessel for a funerary ritual — after all the snake image had a chthonic meaning in many cultures. There was made a conclusion that the jug was decorated not with geometrical but with subject ornament. The aviability of realistic depicted heads of snakes allows recall the Scythian animal style. No one can exclude that the Sarata burial had been made just in the Early Scythian time using the vessel preserved as a relic for a long time. If such observations will receive additional arguments the burial no. 13 of the barrow no. 10 near Sarata could be included in the small group of Early Scythian burials of the Steppe zone. Показаны результаты визуального исследования известного и неоднократно опубликованного кувшина из погребения 13 кургана 10 у с. Сарата на Одещине, раскопанного профессором Киевского университета св. Владимира Ф.И. Кнауэром в 1888—1890 гг. По публикации первых результатов исследований Ф.И. Кнауэра уточняется локализация и состав курганной группы. Приводится описание погребения 13 и сосуда, стоявшего за головой погребенного. Изучение декора кувшина с Сараты de visu в Национальном музее истории Украины позволяет утверждать, что волюты, характерные для культуры Басараби, заканчиваются не просто завитками, как считалось ранее, а двумя головками змей (рис. 4, 3). Правая волюта с головкой змеи была заполнена белой пастой, левая — розовой. Увеличение изображений позволяет предполагать, что головки появились несколько позже. Они нанесены глубокими насечками, а не мелкозубчатым штампом, которым выполнен орнамент сосуда. Белая паста, заполняющая головку змеи, справа более плотная. Указанные наблюдения несколько меняют оценку изображения на сосуде с Сараты. Возможно, речь идет о разновременных изображениях. Так, основная орнаментация была нанесена при изготовлении сосуда в среде культуры Басараби. Изображение головок появилось позже, возможно, при подготовке сосуда к использованию в погребальном ритуале — ведь изображение змей у многих народов имело хтоническое значение. Таким образом, кувшин декорирован не геометрическим, а сюжетным орнаментом. Появление реалистично изображенных головок змей позволяет вспомнить скифский звериный стиль. Возможно, захоронение из Сараты было осуществлено уже в раннескифское время с использованием сосуда, который долгое время хранился как реликвия. Если эти наблюдения получат дополнительные аргументы, захоронение 13 в кургане 10 около с. Сарата можно будет включить в немногочисленную группу раннескифских погребений степной зоны.